Open lower limb fractures in the elderly. Issue 6 (June 2022) - Lancaster, Patrick; Kocialkowski, Cezary; Pearce, Oliver; Khan, Umraz; Riddick, Andrew; Kelly, Michael
Highlights: Elderly open fractures represent a complex clinical problem with outcomes comparable to those seen in patients with a fractured neck of femur. There is limited literature available on the best way to manage open lower limb fractures in the elderly. This paper puts forward a treatment algorithm to help guide management in this complex cohort of patients. Abstract: Objective: The aim of this study was to assess the outcomes of open lower limb fractures in patients aged 65 and over. The primary outcome was mortality at 30 days, and the secondary outcome was reoperation. Methods: This study retrospectively identified patients aged 65 and over, presenting with an open tibia or ankle fracture, over a two-year period. Patient demographics, injury characteristics and surgical interventions were documented. The 30-day and one-year mortality was recorded, as well as any complications encountered. Results: There were 88 patients included in the study, with a mean age of 78 years and 66% of patients were female. Of this cohort, 67 patients (76%) had low energy injuries and 64 patients (73%) had Gustillo-Anderson type IIIB injuries. Treatment consisted of a one-stage surgical procedure in 49 patients (56%) and a two-stage procedure in 37 patients (42%), with two patients dying before definitive treatment. Primary wound closure was performed in 23 patients (26%), four patients (5%) had a split skin graft alone, 35 patients (40%) had local flaps, 21 patients (24%) were managed with free flaps and three patients (3%) had primary below knee amputations. The 30-day mortality rate was 10%, the one-year mortality rate was 19% and the reoperation rate was 8%. Conclusion: Open lower limb fractures in the elderly are a life and limb threatening injury, with a similar demographic and mortality profile to hip fracture. This study demonstrates that limb salvage can be achieved in 93% of cases, with treatment performed as a one-stage procedure in 56% of cases.